META-ANALYSIS: THE IMPROVEMENT NUMERACY LITERACY THROUGH PROBLEM BASED LEARNING - Asani, Fityan; Wardono, Wardono; Dewi (Nino Adhi), Nuriana Rachmani; Mariani, Scolastika; Agoestanto, Arief (Jurnal Pendidikan Matematika dan IPA, 2024)
Numeracy literacy is a very important skill in the 21st century. However, the numeracy literacy rate in Indonesia is still low, this can be seen from the results of the PISA test and various observational studies in schools. One way to overcome this problem is by applying the Problem Based Learning (PBL) model. The aim of this research is to determine the improvement numeracy literacy through the PBL model. The research method used is meta analysis with a sequence of preparation, implementation and analysis stages. The analyzed articles were 10 articles, with the criteria of each article discussing the PBL model for numeracy literacy, and there was information about the mean and standard deviation. The results obtained are that students' numeracy literacy through the PBL model has increased, where . It was concluded that there was a significant difference between the pre-test and post-test literacy numeracy scores before and after the PBL model. The average pre-test and post-test scores are 62.54 and 77.92 respectively, numeracy literacy in the post-test is higher than in the pre-test, so it can be concluded that the PBL model can increase students' numeracy literacy. The articles analyzed have similarities and differences in results and views because many aspects are applied. There were 2 different studies found, both of which received an Effect Size (ES) value of 0.09 and were categorized as small, so further research related to PBL on numeracy literacy, especially at the elementary school level, considering that in this meta analysis only used 1 data with the elementary school level whose results were not significant.